Household Expenditure Sector Inflation from the Perspective of Panca Kumaligi Reincarnation - I Komang Gede; Ida Ayu Putu Sari; Eko Muliansyah; Dewa Nyoman Benni Kusyana; Ida Bagus Purwa Sidemen (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to examine the impact of inflation on household expenditure in Bali through the philosophical lens of Panca Kumaligi reincarnation, integrating macroeconomic analysis with Hindu spiritual values. The main issue addressed is that household expenditure under inflation is commonly analyzed solely from an economic perspective, while cultural and religious dimensions remain largely overlooked. This research employs a multidisciplinary mixed-methods approach conducted over two years. The first year focuses on quantitative analysis using secondary data on inflation, household expenditure, and macroeconomic indicators obtained from official institutions such as Statistics Indonesia and Bank Indonesia. The second year emphasizes qualitative exploration through in-depth interviews, observations, and thematic analysis involving Balinese Hindu households, customary leaders, and religious figures. The findings indicate that inflation significantly affects household expenditure patterns, purchasing power, and consumption priorities. However, in Balinese Hindu society, expenditure decisions are also strongly influenced by spiritual obligations, ritual commitments, and cultural values embedded in Panca Kumaligi philosophy. Inflation often creates a tension between economic rationality and sacred responsibilities, particularly in financing life-cycle ceremonies such as pawiwahan. The study further demonstrates that household financial behavior reflects an ongoing effort to maintain equilibrium between material needs and spiritual harmony. It concludes that integrating macroeconomic analysis with Hindu philosophical perspectives provides a more comprehensive understanding of household expenditure behavior under inflationary pressures. This research contributes to the development of cultural economics and religious economics by offering an innovative conceptual framework that links inflation, household expenditure, and spiritual values within the Balinese Hindu context.